PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. REMCO JAMBI - . Sakinah (Jurnal Ilmiah Dikdaya, 2017)
The contract employees who dominated. The average employee absenteeism without explanation on PT. Remco Jambi 6.55 % as much as. The employees salary in the last five years of increases and most the UMP Jambi province. An average of the development of incentive provided by 1.46 %. The average price of rubber the target in the last five years of 88.92 % with an average of the development of 1.61 %. An average of the development of productivity of employees 275.235. Indicators discipline among others the size of compensation, the whereabouts his exemplary the chief, the whereabouts rules must be and will be used as a handle, leaders courage in taking action, the whereabouts supervision the chief, the whereabouts attention to civil servants a custom that is the creation of the support to discipline. Indicators motivation among other engagement, commitment, satisfaction and turn over. Indicators productivity among other, ability, improve the result is reached, working spirit, self improvement, quality and efficiency. PT. Remco Jambi was a moving company in the fields since 1982 as industry crumb rubber until now, is a product SIR-20 with the quality of exports of sport material needs of natural rubber company supplied by farmers 100 percent from the plantation of the people in the form of rubber slab, a slab lump, cup and lump sit angina both directly and through brokers. Calculation SPPS 20 is Y = 0,433 + 0.245 X1 + 0,832 X2 + e. Thus there is a positive influence between discipline and motivation to employee productivity. Rated R square of 0.830, this shows the influence of the independent variables on the dependent variable. It also explains the variance in the independent variable of 83.10 %, while the remaining 16.90% is explained by other factors Dicipline, motivation and productivity of employees at PT. Remco Jambi high. Based on test the hypothesis in partial known together discipline and motivation influence on productivity of employees. Simultaneously known only discipline that influence productivity of employees at PT. Remco Jambi. While the motivation no impact on productivity of employees at PT. Remco Jambi. Keywords: Discipline, Motivation, Productivity